A systematic review and meta‐analysis of the impact of the left atrial appendage closure on left atrial function. Issue 6 (2nd April 2022) - Mostafa, Mostafa Reda; Magdi, Mohamed; Al‐abdouh, Ahmad; Abusnina, Waiel; Elbanna, Mostafa; Abdelazeem, Basel; Renjithal, Sarath Lal Mannumbeth; Mamas, Mamas A; Shah, Jaffer
Abstract: Background: Left atrial (LA) appendage closure (LAAC) is effective in patients with atrial fibrillation who are not candidates for long‐term anticoagulation. However, the impact of LAAC on LA function is unknown. The aim of this study is to evaluate the impact of LAAC on atrial function. Methods: This meta‐analysis was conducted according to Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines. A search strategy was designed to utilize PubMed/Medline, EMBASE, and Google scholar for studies showing the effect of LAAC on the LA function from inception to November 20, 2021. The standardized mean difference (SMD) was calculated from the means and standard deviations. Results: Of 247 studies initially identified, 8 studies comprising 260 patients were included in the final analysis. There was a significant increase in LA emptying fraction following LAAC compared with preoperative function (SMD: 0.53; 95% confidence interval [CI]: 0.04–1.01; p = .03; I 2 = 75%). In contrast, there were no significant differences in LA volume (SMD: −0.07; 95% CI: −0.82–0.69; p = .86; I 2 = 92%) peak atrial longitudinal strain (SMD: 0.50; 95% CI: −0.08–1.08; p = .09; I 2 = 89%), peak atrial contraction strain (SMD: 0.38; 95% CI: −0.22–0.99; p = .21; I 2 = 81%), strain during atrial contraction (SMD: −0.24; 95% CI: −0.61–0.13; p = .20; I 2 = 0%), strain during ventricular systole (SMD: 0.47; 95% CI: −0.32–1.27; p = .24; I 2 = 89%), strain during ventricular diastole (SMD: 0.09; 95% CI: −0.32–0.51; p = .66; I 2 = 65%). Conclusion: LAAC is associated with improvement in the left atrial emptying fraction, but did not significantly influence other parameters.